Waqf Crowdfunding Dana Ummat as a Framework for Fisherman - Rosida Dwi Ayuningtyas; Yusuf bin Haji Othman; Siti Mudrikah (IAIN Padangsidimpuan, 2022)
Most fishermen in Indonesia have enormous potential, but they are constrained by several things, such as capital constraints and constraints on marketing marine catches. This study aims to provide a concept and idea in the form of the Community Fund Crowdfunding Waqf (WCDU) model. This concept aims to empower fishermen and encourage Nadzhir's programs to be more active and innovative in absorbing opportunities and potential. The research method used is a qualitative approach with a literature review method. The results of this study are proposed ideas illustrated by the Waqf Crowdfunding Community Fund (WCDU) model as an alternative model for alleviating the problems and constraints faced by fishermen. But also ideas regarding the sustainability of the ongoing waqf projects, such as training for fishermen, supervision of waqf project implementation, and evaluation of the benefits of ongoing waqf projects. So the fishermen's waqf program does not stop at the physical realization of the waqf facilities but also the evaluation of the implementation of the waqf project.